2023
DOI: 10.3389/fnut.2023.1228703
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathways and nutrigenomic review of insulin resistance development in gestational diabetes mellitus

Patricia Guevara-Ramírez,
Elius Paz-Cruz,
Santiago Cadena-Ullauri
et al.

Abstract: Gestational diabetes mellitus is a condition marked by raised blood sugar levels and insulin resistance that usually occurs during the second or third trimester of pregnancy. According to the World Health Organization, hyperglycemia affects 16.9% of pregnancies worldwide. Dietary changes are the primarily alternative treatment for gestational diabetes mellitus. This paper aims to perform an exhaustive overview of the interaction between diet, gene expression, and the metabolic pathways related to insulin resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 175 publications
0
2
0
Order By: Relevance
“…It has previously been revealed that diabetes could destroy the control relationships between bacteria, disrupting the human micro-ecological balance, which is conducive to forming pan-resistant species of AB ( Ren et al, 2019 ). The number of pregnant women with pre-existing diabetes was relatively low in the present study, whereas GDM was found to be an independent risk factor for pregnant women who carried the CRAB isolates; GDM also resulted in an increased risk of complications, such as leading to the development of type 2 diabetes in both the mother and infant ( Guevara-Ramírez et al, 2023 ). Infections in pregnancy are common and are associated with numerous consequences for the mother, fetus, and neonate ( Hazenberg et al, 2021 ).…”
Section: Discussionmentioning
confidence: 55%
“…It has previously been revealed that diabetes could destroy the control relationships between bacteria, disrupting the human micro-ecological balance, which is conducive to forming pan-resistant species of AB ( Ren et al, 2019 ). The number of pregnant women with pre-existing diabetes was relatively low in the present study, whereas GDM was found to be an independent risk factor for pregnant women who carried the CRAB isolates; GDM also resulted in an increased risk of complications, such as leading to the development of type 2 diabetes in both the mother and infant ( Guevara-Ramírez et al, 2023 ). Infections in pregnancy are common and are associated with numerous consequences for the mother, fetus, and neonate ( Hazenberg et al, 2021 ).…”
Section: Discussionmentioning
confidence: 55%
“…A recent study by Verde and colleagues demonstrated that strict adherence to the Mediterranean diet prior to starting a VLCKD increases the effectiveness of the VLCKD by helping overweight/obesity-afflicted individuals to lose weight while enhancing their body composition [49]. The authors attributed these outcomes to the existence of bioactive compounds in the Mediterranean diet that may aid in creating an ideal metabolic environment for initiating ketosis [49][50][51][52]. It is noteworthy that the last phase (maintenance stage) of the VLCKD diet is a Mediterranean-style dietary approach [4…”
Section: Vlckd Protocol: Step By Stepmentioning
confidence: 99%